Problems of tonal modeling of objects life in the educational still life - V.V. Dmytrenko (Academy of Cognitive and Natural Sciences, 2006)
In the article the conxidervd qiuxtran of the use of method of imaginary replacement of the articles cf compoundform by combination of simple geometrical bodies, with the purpose of finding of border of chiaroscuro on the surface of domestic objects, during drawing of educational still lives.